Artificial Island Construction Using Large Steel Cylinders. Issue 4 (1st October 2020) - Lin, Ming; Wang, Rukai; Lin, Wei
Abstract: The Hong Kong–Zhuhai–Macao Bridge (HZMB) Island-Tunnel Project consists mainly of two offshore artificial islands that serve as transitions between bridges and an underwater tunnel. The artificial islands lie on the critical path of the entire 55 km long HZMB link. To meet the construction schedule, the authors proposed and implemented a novel method of constructing the artificial islands, using deep-insert steel cylinder piling with auxiliary cells. Using this method, two artificial islands, each with a land area of around 100, 000 m 2, were formed in 6 months, whereas the originally proposed construction methods would have required 3 years. Furthermore, the use of this method in this context minimized the dredging volume required for the artificial island foundations, reduced ship-collision risks and reduced the project's environmental impacts. This approach is now being applied to other projects in China, such as the Shenzhen–Zhongshan Link. This paper discusses the concept and underlying thinking, key technological points and lessons learnt from this work.